2018
DOI: 10.1080/17439760.2018.1424924
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude predicts hope and happiness: A two-study assessment of traits and states

Abstract: Gratitude is the appreciation of a gift received; happiness is the enjoyment of a present good; and hope is the desire for a valued future. Two studies investigated gratitude as a predictor of hope and happiness. In Study 1, hierarchical regressions (N = 181) revealed that trait gratitude exceeded other constructs (forgivingness, patience, self-control) in predicting trait hope and happiness. In Study 2, we experimentally tested the impact of a gratitude-related writing intervention on state hope and happiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 43 publications
4
54
0
5
Order By: Relevance
“…Finally, results indicated that the relationships between these variables were not moderated by gender or adolescence stage (early vs. middle). Consistent with previous studies, forgiveness and gratitude were related to happiness in adolescents (Maltby et al, 2005;0.82 Rana et al, 2014;Witvliet et al, 2018;You et al, 2018). This association may be explained by the influence of forgiveness and gratitude in maintaining positive relationships, which contributes to gaining social support (Hobfoll, 1989;Fredickson, 1998;You et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, results indicated that the relationships between these variables were not moderated by gender or adolescence stage (early vs. middle). Consistent with previous studies, forgiveness and gratitude were related to happiness in adolescents (Maltby et al, 2005;0.82 Rana et al, 2014;Witvliet et al, 2018;You et al, 2018). This association may be explained by the influence of forgiveness and gratitude in maintaining positive relationships, which contributes to gaining social support (Hobfoll, 1989;Fredickson, 1998;You et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“… McCullough et al (2002) argued that people who are full of gratitude and hope will enjoy their lives, and whether they look at the past positively or pursue meaningful future goals, the inner social orientation of gratitude may further promote the generation of hope. Witvliet et al (2019) found that by letting the individuals recall people or things that deserve gratitude in the past, their hope for the future could be effectively improved. Increasing individuals’ hope can help them to distract their attention from negative events, and promote individuals to adopt more adaptive strategies to deal with negative events, thus alleviating depression symptoms ( Snyder, 2002 ; Kaleta and Justyna, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stres yang dirasakan mencerminkan tingkat stres yang dialami sebagai fungsi dari peristiwa stres yang objektif, proses koping dan faktor kepribadian (Cohen, Kamarck, & Mermelstein, 1983 (Lin & Yeh, 2014). Beberapa literatur menyatakan bahwa rasa syukur atau mengingat hal-hal yang disyukuri dapat mendukung peningkatan yang signifikan terhadap kebahagiaan saat ini dan harapan dimasa yang akan datang (Witvliet, Richie, Luna, & Tongeren, 2018).…”
unclassified